Practical Methods of Preparing a Systems Analyst - Rob, Mohammad A (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Systems Analysis and Design (SAD) is a course commonly taught in almost all MIS programs. It is recommended as a required course by all standard curricula of undergraduate and graduate programs. Most students do not recognize the significance of this course until they enter the workforce. The theoretical nature of the course does not lend itself to hands-on activities readily encountered in courses such as programming or database; however, it requires prior knowledge on these subject matters. Thus making this course appealing to students is a difficult task. In this paper, we present a project-based methodology of teaching systems analysis and design that focuses on the development of system documentations that keeps students engaged in key activities of the Systems Development Life Cycle.